Nursing care for patients with mucopolysaccharidosis VI: an integrative literature review (Research, Society and Development, 2022)
Objective: To highlight the needs of patients with Maroteaux-Lamy Syndrome or mucopolysaccharidosis VI, and in the light of this to propose possible nursing diagnoses. Methodology: The research is of a basic nature, descriptive, literature review. In this sense, data were collected from articles in Scielo, BVS and LILACS, between the years 2002 to 2015, where during data collection 1,242 articles were found, and during the selection process, after all filters, they remained 7 articles in all. Therefore, from these 7 articles, the necessary information was collected to elaborate a framework of possible nursing diagnoses. Result: Patients with MPS VI (mucopolysaccharidosis VI) have a higher prevalence of osteoarticular involvement, according to the data collected and analyzed. Therefore, possible nursing diagnoses can be impaired physical mobility, impaired walking, impaired transferability, impaired getting up, impaired sitting. Conclusion: Based on the clinical manifestations found in the literature review, the possible nursing diagnoses aim to maximize the effectiveness of nursing care, since the nursing diagnosis is a crucial step to develop an action plan for the care process of the patient. Therefore, the nurse has this very important role with SAE (Systematization of Nursing Care), as it deals with one of its several attributions.